Nutritional status of institutionalised elderly, with special reference to iron - Atukorala, T.M.; Ranjani, L.P.; Sheriff, M.H.R. (University of Colombo, 1988)
Abstract : Iron and nutritional status were determined in 96 subjects over 60 years of age living in two homes for elders. The first group comprised of 31 males and 31 females, while the second group comprised of 34 females. Their dietary intake of energy, protein and iron was determined using the 24-hour dietary recall method and the iron and nutritional status was assessed using haematological and biochemical parameters. A higher proportion of females than males had deficient energy intakes, while protein intakes were low in both males and females. Iron intakes below the lowest values recommended by the WHO were seen in 7 males (22.6 %) and 40 females (53.3 %). The mean haemoglobin levels were low in both males and females, while a higher percentage of females than males had haemoglobin concentrations less than 10g/dl and transferrin saturation values less than 16%. Plasma ascorbic acid levels in the deficient range were seen in 22 males (76%) and 45 females (79%), while their mean plasma protein concentrations were within the normal range.
Ceylon Journal of Medical Science: 1988; 31(1); 7-17p.